Pemetaan Saintifik terhadap Potensi Tanaman Brassicaceae sebagai Anti-inflamasi: Analisis Bibliometrik Periode Tahun 2003−2024 - Tivanie, Riza Ayu; Murti, Yosi Bayu; Illian, Didi Nurhadi; Nugroho, Agung Endro (Journal of Pharmaceutical and Sciences, 2025)
The Brassicaceae family is recognized for its antioxidant and anti-inflammatory properties. Due to its widespread distribution, it serves as a prominent source of bioactive phytochemicals, attracting considerable research interest. Brassicaceae plants contain several secondary metabolites, including glucosinolates, which are precursors to bioactive compounds like isothiocyanates (e.g., sulforaphane) that have demonstrated anti-inflammatory effects. This study aims to investigate keywords, countries, number of publications, institutions, authors, and journals related to Brassicaceae plants as anti-inflammatory agents during the period 2003–2024 using a comprehensive bibliometric analysis method. Information was collected using the Scopus database, followed by data analysis using the Biblioshiny R Package and VOSviewer. A total of 760 articles meeting the inclusion criteria were analyzed. The results indicate that 2023 saw the largest increase in research publications, with China emerging as the leading contributor, while the USA had the highest citation count. The International Journal of Molecular Sciences was identified as the most popular publishing journal. Kyung Hee University was designated as the most productive institution, with Li Y as the author with the highest contribution. Bibliometric data also highlighted several therapeutic target molecules, including cytokines, nitric oxide, cyclooxygenase-2, and Nrf2, which play crucial roles in the action mechanisms of signature metabolites from Brassicaceae plants, including sulforaphane, isothiocyanates, glucosinolates, and flavonoids, for therapeutic purposes as anti-inflammatory, antioxidant, antimicrobial, and chemopreventive agents. These findings highlight the significant potential of Brassicaceae medicinal plants for various therapeutic mechanisms and provide recommendations for future research in the pharmacy field.